ANALISIS IMPLEMENTASI SISTEM INFORMASI DESA TERINTEGRASI DI KABUPATEN SERANG - Putra, Arta Rusidarma; Silfiana, Silfiana (Jurnal Kebijakan Pembangunan Daerah, 2022)
The role of information technology has provided changes without exception for the Village Government. The implementation of information technology-based services is an obligation in building an Information System based on Law Number 6 of 2014. The Serang Regency area as an autonomous region is also expected to be able to implement a Village Information System. This study aims to map the implementation of village information system policies in Serang Regency. The method used in this research is descriptive qualitative data sourced from secondary data and primary data analysis using an interactive model. The results showed that the implementation of Information Systems in Serang Regency had not run optimally due to weaknesses in coordination, aspects of resources, disposition and bureaucratic structure; the impact of information System Implementation in Serang Regency had not been enjoyed by all villages in Serang Regency; and there are supporting factors in Information System Implementation including the availability of budget allocations, clear division of tasks for each stakeholder, and complete Village Information System content. Keywords: Policy Implementation, Village Information System, Serang Regency